Supported Accommodations for People with Serious Mental Disorders: Staff’s Assessment of Work Challenges and Their Impact during COVID-19 - Pedrosa,Bárbara (2024)
Abstract Introduction: Few studies analysed the impact of COVID-19 on supported accommodations (SAs) for people with serious mental disorders. This study aimed to analyse staff’s assessments of work challenges in SAs during COVID-19, the impact of the pandemic on staff, their perception of the impact on residents, and associated factors. Methods: To assess work challenges and the impact of the pandemic on staff and their perception of the impact on residents, a questionnaire was administered to the staff of SAs. Multilevel logistic regression analyses were conducted, involving work challenges and staff’s sociodemographic characteristics, and impact on staff. Results: In total, 117 staff from 32 SAs responded. A challenging environment was felt by most participants (68.4%). There were significant differences in work challenges experienced by staff, namely, according to profession and years working in mental health. A negative impact of COVID-19 was reported by 26.5% of staff, which was associated with their feeling that residents were no longer getting an acceptable service (OR = 7.04, 95% CI 1.43, 34.65, p = 0.016) and with staff feeling at risk of infection at work (OR = 7.99, 95% CI 1.39, 45.86, p = 0.020). Relapse and deterioration of residents’ mental health were perceived by 43.6% of staff. Conclusions: Several work challenges occurred in SAs during COVID-19, which had a negative impact on staff and reportedly on residents. Implications range from the organisational to the clinical levels and may apply internationally and in similarly challenging situations.